Analisis Kajian Pengelolaan Mutu Pendidikan SD Tunas Lestari Sungai Basung - Fina Febriyanti; Asep Awaludin; Titi Haryati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyse the management of education quality at SD Tunas Lestari Sungai Basung, Damai sub-district, West Kutai district. Education quality is a fundamental aspect in the delivery of quality and sustainable education services. This study focuses on the implementation of the eight National Education Standards (SNP), which include standards of content, process, graduate competencies, educators and education personnel, infrastructure, management, financing and assessment. The research method used was descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation studies. The research informants consisted of principals, teachers, education personnel and school committees. The results showed that in general SD Tunas Lestari has tried to fulfil the standards of education quality management, especially in the aspects of internal management and learning processes. However, there are still obstacles such as limited human resources that have not been certified, unavailable internet access, and minimal use of technology in learning. In addition, the implementation of Merdeka Curriculum and P5 activities has not been optimal due to teachers' lack of conceptual understanding. This study recommends strengthening teachers' capacity through continuous training, improving support for learning facilities and implementing data-based management using the Education Report Card as the basis for quality planning. Effective education quality management requires synergy between the principal, teachers, committees and other stakeholders so that the goal of quality education can be achieved.